Hermeneutics and texts: the challenge of translation - Rios-Delgado, Teresa Jesús (2022)
The research work analyzes hermeneutics as translation, relating both concepts, focusing on human being’ different visions of reality, world, and actions to basically justify its behavior or way of life. Likewise, the hermeneutical perspective of translation is established based on authors such as Wittgenstein, Ricoeur and Gadamer, where the text is the core of comprehension and interpretation. The translator is not only the bridge between two worlds, but is also the interpreter of reality in both languages and is responsible for an interpretation that reflects the understanding and acceptance of these realities. Finally, in our opinion, the main challenges of translation in the interpreting activity are presented, enhanced with examples of the types of texts to be translated. Hermeneutics allows us to see signs beyond just indicators or language as a simple means of expression, rather, it challenges a one-to-one relationship between human beings and language.